Question
upstudy study bank question image url

Simplify the following without the use of a calculator: \( \frac{\cos \left(40^{\circ}-x\right) \cos x-\sin \left(40^{\circ}-x\right) \sin x}{\sin 205^{\circ} \cos 155^{\circ}} \) Calculate the value of \( \frac{\cos 2^{\circ}+\sqrt{3} \sin \left(-2^{\circ}\right)}{4 \sin 346^{\circ} \cos 194^{\circ}} \) without the use of a calculator.

Ask by Marsh Daniel. in South Africa
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The first expression simplifies to 2, and the second expression evaluates to 1.

Solution

We will simplify each expression step‐by‐step. ───────────────────────────── 1) Simplify   ( cos(40° – x) cos x – sin(40° – x) sin x ) / ( sin205° · cos155° ). Step 1.1. Simplify the numerator. Recall the cosine addition formula:   cos A cos B – sin A sin B = cos(A + B). Here, let A = (40° – x) and B = x. Then:   cos(40° – x) cos x – sin(40° – x) sin x = cos[(40° – x) + x] = cos 40°. Step 1.2. Simplify the denominator. Examine sin205°:   205° = 180° + 25° → sin205° = – sin25°. Examine cos155°:   155° = 180° – 25° → cos155° = – cos25°. So, their product is:   sin205° · cos155° = (– sin25°)(– cos25°) = sin25° cos25°. Step 1.3. Write the simplified expression. We now have:   cos40° / (sin25° cos25°). Step 1.4. Use the double-angle identity. Note that:   2 sin25° cos25° = sin50° → sin25° cos25° = sin50°/2. Thus, the expression becomes:   cos40° / (sin50°/2) = (2 cos40°) / sin50°. Step 1.5. Recognize the co-function relationship. Since cos40° = sin(90° – 40°) = sin50°, we have:   (2 cos40°) / sin50° = 2(sin50°)/ sin50° = 2. So the first expression simplifies to 2. ───────────────────────────── 2) Calculate   ( cos2° + √3 sin(–2°) ) / ( 4 sin346° · cos194° ). Step 2.1. Simplify the numerator. Notice that sin(–2°) = – sin2°. Therefore:   cos2° + √3 sin(–2°) = cos2° – √3 sin2°. Factor a 2 in a clever way by writing:   cos2° – √3 sin2° = 2[(1/2) cos2° – (√3/2) sin2°]. Recall that cos60° = 1/2 and sin60° = √3/2. Hence:   (1/2) cos2° – (√3/2) sin2° = cos2° cos60° – sin2° sin60° = cos(2° + 60°) = cos62°. Thus, the numerator becomes:   2 cos62°. Step 2.2. Simplify the denominator. First, consider sin346°:   346° = 360° – 14° → sin346° = – sin14°. Next, cos194°:   194° = 180° + 14° → cos194° = – cos14°. So, their product is:   sin346° · cos194° = (– sin14°)(– cos14°) = sin14° cos14°. Thus, the denominator becomes:   4 sin14° cos14°. Use the double-angle identity:   2 sin14° cos14° = sin28° → 4 sin14° cos14° = 2 sin28°. Step 2.3. Combine the results. Now the expression is:   (2 cos62°) / (2 sin28°) = cos62° / sin28°. Step 2.4. Use a co-function identity. Since sin28° = cos(90° – 28°) = cos62°, we find:   cos62° / sin28° = cos62° / cos62° = 1. So the second expression evaluates to 1. ───────────────────────────── Final Answers: 1) The expression simplifies to 2. 2) The value of the second expression is 1.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To simplify the fraction \( \frac{\cos \left(40^{\circ}-x\right) \cos x-\sin \left(40^{\circ}-x\right) \sin x}{\sin 205^{\circ} \cos 155^{\circ}} \), we can employ the cosine angle subtraction formula: \[ \cos(A - B) = \cos A \cos B + \sin A \sin B. \] In our case, \( A = 40^{\circ} \) and \( B = x \). Thus, \[ \cos(40^{\circ} - x) \cos x - \sin(40^{\circ} - x) \sin x = \cos(40^{\circ} + x). \] Now, for the denominator: \[ \sin 205^{\circ} = \sin(180^{\circ} + 25^{\circ}) = -\sin 25^{\circ}, \] and \[ \cos 155^{\circ} = \cos(180^{\circ} - 25^{\circ}) = -\cos 25^{\circ}. \] Thus, \[ \sin 205^{\circ} \cos 155^{\circ} = (-\sin 25^{\circ})(-\cos 25^{\circ}) = \sin 25^{\circ} \cos 25^{\circ} = \frac{1}{2} \sin(50^{\circ}). \] Now, substituting back, the expression simplifies to: \[ \frac{\cos(40^{\circ} + x)}{\frac{1}{2} \sin(50^{\circ})} = \frac{2 \cos(40^{\circ} + x)}{\sin(50^{\circ})}. \] We know that \( \sin(50^{\circ}) = \cos(40^{\circ}) \), thus finally, the entire expression simplifies to: \[ \frac{2 \cos(40^{\circ} + x)}{\cos(40^{\circ})}. \] Next, we calculate \( \frac{\cos 2^{\circ} + \sqrt{3} \sin(-2^{\circ})}{4 \sin 346^{\circ} \cos 194^{\circ}} \). First, let’s simplify the numerator: \[ \sin(-2^{\circ}) = -\sin 2^{\circ}, \] Thus, \[ \cos 2^{\circ} + \sqrt{3} \sin(-2^{\circ}) = \cos 2^{\circ} - \sqrt{3}\sin 2^{\circ}. \] For the denominator: \[ \sin 346^{\circ} = \sin(360^{\circ} - 14^{\circ}) = -\sin 14^{\circ}, \] and \[ \cos 194^{\circ} = \cos(180^{\circ} + 14^{\circ}) = -\cos 14^{\circ}. \] Thus, \[ 4 \sin 346^{\circ} \cos 194^{\circ} = 4 (-\sin 14^{\circ})(-\cos 14^{\circ}) = 4 \sin 14^{\circ} \cos 14^{\circ} = 2 \sin 28^{\circ}. \] Finally, putting it all together, we have: \[ \frac{\cos 2^{\circ} - \sqrt{3} \sin 2^{\circ}}{2 \sin 28^{\circ}}. \] We can further simplify if needed, but this represents the expression without a calculator.

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy